Toughened composite diaphragm material and preparation method thereof
By adopting a toughened composite diaphragm material with a multi-layer structure, combining the corrosion-resistant layer of high-purity fluoroplastic and flexible fibers with a back film of modified silicone rubber, the problems of prone to rupture and short life of the existing diaphragm materials are solved, and higher toughness, durability and safety are achieved.
Patent Information
- Application Number
- CN202411893527.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
Due to high cycle fatigue and rigid impact, the diaphragm materials of existing diaphragm pumps have low life and are prone to rupture, resulting in pollution, corrosion and shutdown of work and maintenance problems. Especially when dealing with strong acid and strong alkali liquids, there is a risk of serious personal damage.
A toughened composite diaphragm material with a multi-layer structure, including a corrosion-resistant layer and a modified silicone rubber backing film. The corrosion-resistant layer consists of a high-purity fluoroplastic outer protective layer and a fluoroplastic matrix reinforcement layer, and the reinforcement layer is doped with flexible fibers to improve mechanical properties. The back film is a modified silicone rubber, and the interface affinity and material durability are enhanced by plasma modification and the addition of polyethyl acrylate.
It improves the toughness, fatigue resistance and impact resistance of the diaphragm material, extends the service life of the diaphragm, reduces the risk of rupture and maintenance, and ensures safety and reliability in a strong acid and strong alkali environment.
Smart Images

Figure BDA0005201179420000081 
Figure BDA0005201179420000091
Abstract
Description
Technical Field
[0001] The present application relates to a toughened composite diaphragm material and a preparation method thereof, belonging to the technical field of diaphragm pump materials. Background Art
[0002] Diaphragm pumps are pumps that achieve fluid flow through the reciprocating motion of a diaphragm. Diaphragm pumps have good self-priming capabilities and can handle high-viscosity liquids. They can operate without fluid without damage and are widely used in semiconductors, chemicals, pharmaceuticals, food processing, sewage treatment, mining, and many other industrial fields. The design and operation of diaphragm pumps make them a versatile and reliable fluid handling equipment, especially suitable for applications that have special requirements for the sealing and safety of the pump.
[0003] However, the core performance of the diaphragm pump is also restricted by the elastic diaphragm: the diaphragm of the existing diaphragm pump is commonly made of fluoroplastic, which is a flexible material. The high-cycle fatigue and rigid impact generated by the long-term operation of the diaphragm often make the diaphragm life shorter than the designed service life of the diaphragm pump. Once the diaphragm ruptures, it will cause pollution, corrosion, and shutdown maintenance. Since diaphragm pumps often involve the transportation of liquids such as strong acids and alkalis, the aging and rupture of the diaphragm may even cause serious personal injury. Therefore, a diaphragm material with strong toughness is urgently needed. Summary of the invention
[0004] In order to solve the above problems, the present application proposes a toughened composite diaphragm material and a preparation method thereof. By limiting the diaphragm material to a multi-layer structure and modifying the diaphragm material with fillers, the toughness and flexibility of the diaphragm material are improved, making the diaphragm material more durable.
[0005] According to one aspect of the present application, a toughened composite diaphragm material is provided, comprising:
[0006] The corrosion-resistant layer comprises an outer protective layer and a reinforcing layer; the outer protective layer is made of high-purity fluoroplastic, and the reinforcing layer is based on fluoroplastic; the reinforcing layer is doped with flexible fibers; and a back film is made of modified silicone rubber.
[0007] The outer protective layer is made of high-purity fluoroplastics, which can provide protection for the inner layers in strong acids, alkalis and organic solvents without being corroded or penetrated. However, high-purity fluoroplastics are very rigid and are prone to rupture under the action of periodic stress. The reinforcement layer is based on fluoroplastics and doped with flexible fibers, which can enhance the mechanical properties of the corrosion-resistant layer, increase shear stress and crack resistance, and not only improve the dimensional stability and dynamic efficiency of fluoroplastics, and provide better control performance for diaphragm materials, but also can be processed into an integral material with the outer protective layer, avoiding the problem of interlayer separation caused by the difficulty of compounding with materials due to the chemical stability of fluoroplastics. The back film is an elastomer, which provides good flexibility and resilience.
[0008] Specifically, the fluoroplastic includes any one of polytetrafluoroethylene, polyperfluoroethylene propylene, polyperfluoroalkoxy resin and polychlorotrifluoroethylene.
[0009] Optionally, the aspect ratio of the flexible fiber is (60-100): 1. The aspect ratio of the reinforcing fiber determines its modification of the matrix material. Too short reinforcing fibers not only fail to provide higher toughness, but increase the hardness and stiffness of the material, causing the material to be more prone to rupture under the action of impact force; too long reinforcing fibers are difficult to disperse in the matrix material, resulting in poor material uniformity, excessive concentration of local stress, and poor impact resistance of the material.
[0010] Optionally, the mass of the flexible fibers in the reinforcement layer accounts for 8-15%.
[0011] If the amount of flexible fiber added is too low, it will be difficult to play a toughening role; if the amount added is too high, it will be difficult to disperse and at the same time destroy the bond with the outer protective layer.
[0012] Optionally, the flexible fiber includes at least one of aramid fiber, SiOC aerogel / flexible ceramic fiber, and polyimide fiber.
[0013] The flexible fiber can be sintered and composited with fluoroplastics, has chemical stability, and provides excellent performance gain.
[0014] Optionally, the reinforcement layer is modified by plasma on the side in contact with the back film.
[0015] A large number of free radicals are generated on the surface of plasma-modified fluoroplastics, and better adhesion can be obtained; plasma modification only affects the surface properties of the material, and thus does not affect the properties of the reinforcement layer material itself.
[0016] Optionally, the plasma-modified gas is one of H2, Ar, He or acrylic acid gas.
[0017] The gases can all efficiently modify fluoroplastics.
[0018] Preferably, the plasma-modified gas is acrylic acid gas, which as a plasma gas not only has a surface activation effect but also can perform graft modification on the surface of fluoroplastics.
[0019] Optionally, the modified silicone rubber material is prepared from the following components in parts by weight: 60 to 70 parts of methyl divinyl silicone rubber, 5 to 10 parts of ethyl acrylate monomer, 6 to 8 parts of cross-linking agent, 20 to 30 parts of reinforcing filler, 1 to 2.5 parts of silane coupling agent, 0.2 to 1.5 parts of vulcanizing agent, and 0.2 to 1.2 parts of catalyst.
[0020] The backing glue is based on silicone rubber and can be compounded with plasma-modified fluoroplastics to achieve better bonding between the reinforcing layer and the elastomer; the addition of ethyl acrylate monomers to form long polymer chains during the vulcanization process can disperse stress and increase the fatigue threshold of silicone rubber; at the same time, the addition of ethyl acrylate has affinity with acrylic acid-modified fluoroplastics, thereby increasing the bonding strength between the backing film and the corrosion-resistant layer.
[0021] Specifically, the silane coupling agent is at least one of hydroxy silicone oil, hexamethyldisilazane, vinyltriethoxysilane or γ-mercaptopropyltriethoxysilane;
[0022] The vulcanizing agent is at least one of benzoyl peroxide, dicumyl peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane peroxide.
[0023] Specifically, the crosslinking agent is tricyclodecane acrylate containing two CC double bonds (tricyclo[5.2.1.02,6]decane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate); the reinforcing filler is one of carbon black or fumed silica; and the catalyst is a platinum catalyst.
[0024] According to another aspect of the present application, a method for preparing a toughened composite diaphragm material is provided, which is used to prepare the toughened composite diaphragm material, comprising the following steps:
[0025] (1) mixing fluoroplastic powder and flexible fiber, cold pressing and sintering to obtain a reinforcement layer;
[0026] (2) cold pressing and sintering the fluoroplastic powder on the reinforcement layer to obtain a corrosion-resistant layer having a thickness of 1.5 to 3 mm;
[0027] (3) Prefabricated backing film;
[0028] (4) The reinforcing layer and the back film are bonded and compounded with polyurethane glue or silicone glue to obtain a toughened composite diaphragm material.
[0029] Specifically, the prefabrication process of the backing film in step (3) is to fully mix methyl divinyl silicone rubber, reinforcing filler, silane coupling agent, and ethyl acrylate monomer, add a crosslinking agent, a vulcanizing agent, and a catalyst, mix them evenly, pour them into a mold, and vulcanize them at room temperature to obtain a backing film, and the thickness of the backing film is 3 to 4 mm;
[0030] Optionally, the cold pressing pressure in step (1) is 20-30 MPa and the sintering temperature is 350-380° C.
[0031] It also includes plasma surface treatment of one side of the reinforcement layer of the corrosion-resistant layer after obtaining the corrosion-resistant layer; the plasma surface treatment process is to react for 20 to 40 seconds at room temperature and a 15 to 50Pa gas atmosphere, and the discharge power of the discharge power supply is 80 to 120W.
[0032] The beneficial effects of this application include but are not limited to:
[0033] 1. The toughened composite diaphragm material provided in the present application, by providing a corrosion-resistant layer consisting of an outer protective layer and a reinforcement layer and a modified silicone rubber back film, makes the diaphragm material not only have strong corrosion resistance, but also have excellent toughness and fatigue resistance.
[0034] 2. The toughened composite diaphragm material provided in the present application, through the fluoroplastic doped with flexible fibers, not only has good bonding with the outer protective layer, but also provides higher toughness and tear resistance, thereby improving the impact resistance of the corrosion-resistant layer.
[0035] 3. The toughened composite diaphragm material provided in the present application enhances the affinity between the interfaces by plasma-modifying the contact surface between the reinforcement layer and the back film and doping polypropylene ethyl ester into the silicone rubber, making the bonding between the reinforcement layer and the back film more stable and less likely to separate, thereby improving the durability of the diaphragm material. DETAILED DESCRIPTION
[0036] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0037] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0038] Example 1
[0039] The preparation method of the toughened composite diaphragm material comprises the following steps:
[0040] (1) 85 parts of polytetrafluoroethylene powder and 15 parts of aramid fiber (diameter 1 μm, aspect ratio 60:1) were mixed, cold pressed at 30 MPa, and sintered at 380°C to obtain a reinforcement layer;
[0041] (2) cold pressing and sintering 100 parts of polytetrafluoroethylene powder on the reinforcement layer (the cold pressing pressure and the sintering temperature are the same as those in step (1)) to obtain a corrosion-resistant layer, the thickness of the corrosion-resistant layer being 2.5 mm;
[0042] (3) Prefabricated backing film:
[0043] After 70 parts of methyl divinyl silicone rubber, 30 parts of carbon black, 2.5 parts of hydroxy silicone oil and 10 parts of ethyl acrylate monomer are fully mixed, 8 parts of tricyclodecane acrylate, 1.5 parts of benzoyl peroxide and 1.5 parts of chloroplatinic acid are added, the mixture is evenly poured into a mold and vulcanized at room temperature to obtain a back film having a thickness of 4 mm;
[0044] (4) The reinforcing layer and the back film are bonded and compounded with polyurethane glue to obtain a toughened composite diaphragm material 1#.
[0045] Example 2
[0046] (1) 92 parts of polytetrafluoroethylene powder and 8 parts of SiOC aerogel / flexible ceramic fiber (diameter 5 μm, aspect ratio 100:1) were mixed, cold pressed at 20 MPa, and sintered at 350 °C to obtain a reinforcement layer;
[0047] (2) cold pressing and sintering 100 parts of polytetrafluoroethylene powder on the reinforcement layer (the cold pressing pressure and the sintering temperature are the same as those in step (1)) to obtain a corrosion-resistant layer, the thickness of the corrosion-resistant layer being 2.5 mm;
[0048] (3) Prefabricated backing film:
[0049] After 60 parts of methyl divinyl silicone rubber, 5 parts of white carbon black, 1 part of hydroxy silicone oil, and 5 parts of ethyl acrylate monomer are fully mixed, 6 parts of tricyclodecane acrylate, 0.2 parts of benzoyl peroxide, and 0.2 parts of chloroplatinic acid are added, the mixture is evenly poured into a mold and vulcanized at room temperature to obtain a back film, and the thickness of the obtained back film is 4 mm;
[0050] (4) The reinforcing layer and the back film are bonded together with silicone adhesive to obtain a toughened composite diaphragm material 2#.
[0051] Example 3
[0052] (1) 90 parts of polytetrafluoroethylene powder and 10 parts of polyimide fiber (diameter 3 μm, aspect ratio 80:1) were mixed, cold pressed at 25 MPa, and sintered at 370°C to obtain a reinforcement layer;
[0053] (2) cold pressing and sintering 100 parts of polytetrafluoroethylene powder on the reinforcement layer (the cold pressing pressure and the sintering temperature are the same as those in step (1)) to obtain a corrosion-resistant layer, the thickness of the corrosion-resistant layer being 2.5 mm;
[0054] (3) Prefabricated backing film:
[0055] After 65 parts of methyl divinyl silicone rubber, 8 parts of white carbon black, 1.5 parts of hydroxy silicone oil and 5 parts of ethyl acrylate monomer are fully mixed, 7 parts of tricyclodecane acrylate, 0.8 parts of benzoyl peroxide and 1 part of chloroplatinic acid are added, the mixture is evenly poured into a mold and vulcanized at room temperature to obtain a back film having a thickness of 4 mm;
[0056] (4) The reinforcing layer and the back film are bonded together with silicone adhesive to obtain a toughened composite diaphragm material 3#.
[0057] Example 4
[0058] The difference from Example 3 is that one side of the reinforcement layer of the obtained corrosion-resistant layer is reacted in a 50Pa acrylic acid gas atmosphere for 30s with a discharge power of 100W to prepare a toughened composite diaphragm material 4#.
[0059] Example 5
[0060] The difference from Example 4 is that the aspect ratio of the polyimide fiber used is 20:1, and the toughened composite diaphragm material 5# is prepared.
[0061] Example 6
[0062] The difference from Example 4 is that 10 parts of polyimide fibers are replaced by 50 parts of polyimide fibers to prepare toughened composite diaphragm material 6#.
[0063] Example 7
[0064] The difference from Example 4 is that the polyimide fiber is replaced by nylon fiber to prepare the toughened composite diaphragm material 7#.
[0065] Example 8
[0066] The difference from Example 4 is that a toughened composite diaphragm material 8# is prepared by using a silicone glue composite back film and a corrosion-resistant layer.
[0067] Example 9
[0068] The difference from Example 4 is that no ethyl acrylate monomer is added to the back film to prepare the toughened composite diaphragm material 9#.
[0069] Example 10
[0070] The difference from Example 4 is that no silane coupling agent is added to the back film, and a toughened composite diaphragm material 10# is prepared.
[0071] Embodiment 11
[0072] The difference from Example 4 is that the sintering temperature is 450° C., and a toughened composite diaphragm material 11# is prepared.
[0073] Example 12
[0074] The difference from Example 4 is that the plasma treatment time is 3 minutes, and the toughened composite diaphragm material 12# is prepared.
[0075] Embodiment 13
[0076] The difference from Example 4 is that the surface of the reinforcement layer is plasma modified in a He atmosphere to prepare a toughened composite diaphragm material 13#.
[0077] Comparative Example 1
[0078] The difference from Example 4 is that 90 parts of polytetrafluoroethylene powder and 10 parts of polyimide fibers are replaced with 100 parts of polytetrafluoroethylene powder to prepare a toughened composite diaphragm material D1#.
[0079] Comparative Example 2
[0080] The difference from Example 4 is that a natural rubber with a thickness of 4 mm is used as the backing film to prepare the toughened composite diaphragm material D2#.
[0081] Comparative Example 3
[0082] The difference from Example 4 is that no white carbon black is added to the back film, and a toughened composite diaphragm material D3# is prepared.
[0083] Experimental example
[0084] The various properties of the diaphragm pump diaphragms provided in the embodiments and comparative examples of the present invention were tested. The elongation at break and the tensile strength were tested according to GB / T 1040.1-2018, the flexural test was tested according to GB / T 41937-2022, and the shear strength was tested according to GB / T33334-2016. The following table shows the test results of the various properties of the embodiments and comparative examples:
[0085] Table 1
[0086]
[0087]
[0088] From the above data, it can be seen that the elongation at break and tensile strength of the composite diaphragm material obtained in this scheme are improved, which proves that the composite material has good toughness and high strength; the number of flexures is increased and the durability is good; the material that has been surface treated and modified with silicone rubber has stronger shear strength, and has significant composite effect and production reliability.
[0089] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0090] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A toughened composite diaphragm material, characterized in that: include: The corrosion-resistant layer comprises an outer protective layer and a reinforcing layer; the outer protective layer is made of high-purity fluoroplastic, and the reinforcing layer is based on fluoroplastic; The reinforcing layer is doped with flexible fibers; The backing film is made of modified silicone rubber.
2. The toughened composite diaphragm material according to claim 1, characterized in that: The diameter of the flexible fiber is 1-5 μm, and the aspect ratio is (60-100):
1.
3. The toughened composite diaphragm material according to claim 1, characterized in that: The mass of the flexible fibers accounts for 8-15% of the mass of the reinforcement layer.
4. The toughened composite diaphragm material according to claim 1, characterized in that: The flexible fiber includes at least one of aramid fiber, SiOC aerogel / flexible ceramic fiber, and polyimide fiber.
5. The toughened composite diaphragm material according to claim 1, characterized in that: The reinforcement layer is modified by plasma on the side in contact with the back film.
6. The toughened composite diaphragm material according to claim 5, characterized in that: The plasma modified gas is one of H2, Ar, He or acrylic acid gas.
7. The toughened composite diaphragm material according to claim 1, characterized in that: The modified silicone rubber material is prepared from the following components in parts by weight: 60 to 70 parts of methyl divinyl silicone rubber, 5 to 10 parts of ethyl acrylate monomer, 6 to 8 parts of crosslinking agent, 20 to 30 parts of reinforcing filler, 1 to 2.5 parts of silane coupling agent, 0.2 to 1.5 parts of vulcanizing agent, and 0.2 to 1.2 parts of catalyst.
8. A method for preparing a toughened composite diaphragm material, used for preparing the toughened composite diaphragm material according to claims 1 to 7, characterized in that: The following steps are involved: (1) mixing fluoroplastic powder and flexible fiber, cold pressing and sintering to obtain a reinforcement layer; (2) cold pressing and sintering the fluoroplastic powder on the reinforcement layer to obtain a corrosion-resistant layer; (3) Prefabricated backing film; (4) The reinforcing layer and the back film are bonded and compounded with polyurethane glue or silicone glue to obtain a toughened composite diaphragm material.
9. The method for preparing a toughened composite diaphragm material according to claim 8, characterized in that: The cold pressing pressure in step (1) and step (2) is 20-30 MPa and the sintering temperature is 350-380°C.
10. The method for preparing a toughened composite diaphragm material according to claim 8, characterized in that: It also includes plasma surface treatment of one side of the reinforcement layer of the corrosion-resistant layer after obtaining the corrosion-resistant layer; the plasma surface treatment process is to react for 20 to 40 seconds at room temperature and a 15 to 50Pa gas atmosphere, and the discharge power of the discharge power supply is 80 to 120W.
Citation Information
Patent Citations
Acrylic acid modified vinyl polysiloxane, foam silicone rubber and preparation method of acrylic acid modified vinyl polysiloxane
CN117004028A
Diaphragm of diaphragm pump
CN210799305U
Composite diaphragm of diaphragm pump
CN220929635U
Non-porous adherent inert coatings and methods of making
US20070190329A1
Membrane pump
US20150330383A1